Prevalence of asymptomatic Plasmodium infections with sub-microscopic parasite densities in the northwestern border of Thailand: a potential threat to malaria elimination - Jetsumon Sattabongkot; Chayanut Suansomjit; Wang Nguitragool; Jeeraphat Sirichaisinthop; Saradee Warit; Montip Tiensuwan; Sureemas Buates (Malaria Journal, 2018)
Abstract Background Asymptomatic infections with sub-microscopic Plasmodium serve as a silent reservoir of disease, critical to sustaining a low level of remanent malaria in the population. These infections must be effectively identified and targeted for elimination. The sensitivity of light microscopy, the traditional method used for diagnosing Plasmodium infections, is frequently insufficient for detecting asymptomatic infections due to the low density of parasitaemia. The objective of this study was to explore the current prevalence of asymptomatic sub-microscopic Plasmodium carriages to evaluate the parasite reservoir amongst residents from 7 hamlets in Tak Province in northwestern Thailand using a highly sensitive molecular method. Methods Malaria infection was screened in a real-world setting from 3650 finger-prick blood specimens collected in a mass cross-sectional survey using light microscopy and loop-mediated isothermal amplification (LAMP). LAMP results were later confirmed in a laboratory setting in Bangkok using nested PCR, restriction enzyme digestion and DNA sequencing. The association of malaria infection with demographic factors was explored. Results Parasite prevalence was 0.27% (10/3650) as determined by microscopy. Sub-microscopic infection prevalence was 2.33% (85/3650) by LAMP. Of these, 30.6% (26/85) were infected with Plasmodium falciparum, 52.9% (45/85) with Plasmodium vivax, 2.4% (2/85) with Plasmodium malariae, 4.7% (4/85) with mixed P. falciparum and P. vivax, and 9.4% (8/85) had parasite densities too low for species identification. Asymptomatic carriages (T < 37.5 °C) accounted for 95% (76/80) of all sub-microscopic cases with the highest prevalence occurring in the subjects 31–45 years of age (p ≤ 0.035). Participants working on plantations or as merchants had an increased infection risk. Evaluation by microscopy identified 10.53% (10/95) of all Plasmodium infected participants. Conclusion Participants carrying asymptomatic Plasmodium infections with sub-microscopic parasite ...